Amplifier cooling system / Muhamad Rahmad Yusuf and Mohd Halmi Babas - Yusuf, Muhamad Rahmad; Babas, Mohd Halmi (2004)
IC is stand for Integrated Circuit. IC is very important device in any electronic circuit especially in amplifier circuit. It use for various purpose. When an IC operated in any electronic circuit, it will reach maximum heat temperature. IC will ruin if there are no cooler system. A lot of invention had created, but still cannot overcome this problem. So, after we had done some research, we had created one cooler system. We use this cooler system in amplifier circuit. We name it Amplifier Cooling System. The main reason of making this project is to decrease the temperature of any kind of electronic circuit that used Integrated Circuit (IC). As our project completed, there is no more problem occur when water has been supplied through ‘heat sink’. Then water will flow out by small plastic tube. This process will continuously till the circuit is shut off. For protection of our circuit, we have provided water detector circuit that will cut off the voltage supply to water pump motor. Automatically water will stop flow and for enhanced this circuit will be support by a small 12V fan